Insuficiência renal em pacientes com mieloma múltiplo: uma revisão integrativa - Dantas, Larissa Aguiar (2023)
Multiple myeloma (MM) is a plasma cell disorder that accounts for approximately 10% of hematological neoplasms. It is characterized by the abnormal proliferation of plasma cells, the production of abnormal monoclonal immunoglobulin (also known as M protein), and abnormal light chain proteins. Age, sex, race, and family history are among the main risk factors for MM. According to the International Myeloma Working Group (IMWG), the diagnosis of MM requires the presence of at least one "CRAB" criterion, which is an acronym representing the main clinical manifestations of the disease. One of these criteria is Renal Insufficiency (RI), which is a common consequence in patients diagnosed with MM and can vary depending on the degree of renal damage. The incidence of the disease and the number of deaths associated with MM have been increasing due to delays in effective and early diagnosis in the early stages of the disease or even in its pre-malignant phase. Therefore, this present study aims to conduct a systematic review on the prevalence of renal insufficiency in patients diagnosed with multiple myeloma, considering the underlying pathogenic factors, the main characteristics of MM, the primary diagnostic methods, established biomarkers, and prognostic factors of the disease.